2019
DOI: 10.1111/jam.14287
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal and cytotoxic activity of a diarylheptanoid (etlingerin) isolated from a ginger ( Etlingera pubescens ) endemic to Borneo

Abstract: Aims The aim of this study was to investigate the antimicrobial activities of Etlingera pubescens, and to isolate and identify the antimicrobial compound. Methods and Results The crude extracts of E. pubescens were obtained through methanol extraction, and evaluated for antimicrobial activities. From this extract, 1,7‐bis(3,4‐dihydroxyphenyl)heptan‐3‐yl acetate (etlingerin) was isolated. When compared to curcumin (a compound with a similar chemical structure), etlingerin showed twofold lower minimum inhibitory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 23 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…Staphylococcus aureus (Daniel-Jambun et al 2019). Etlingera pavieana has potential as an anti-inflammatory effect from rhizome extract and its phenolic compounds (Srisook et al 2017).…”
Section: Author Contributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Staphylococcus aureus (Daniel-Jambun et al 2019). Etlingera pavieana has potential as an anti-inflammatory effect from rhizome extract and its phenolic compounds (Srisook et al 2017).…”
Section: Author Contributionmentioning
confidence: 99%
“…Etlingera pavieana has potential as an anti-inflammatory effect from rhizome extract and its phenolic compounds (Srisook et al 2017). Etlingera pubescens, endemic to Borneo, can potentially be a bactericidal and cytotoxic activity of a diarylheptanoid (etlingerin) (Daniel-Jambun et al 2019).…”
Section: Author Contributionmentioning
confidence: 99%
“…Many species are useful to humans as food, seasoning, medicine, or as ornamental plants [1]. Many study findings that Etlingera have been to exhibit pharmacological properties, including antibacterial [2], antidiabetic [3], cytotoxic action [4], protective impact against mercury chloride poisoning [5], and antioxidant [6].…”
Section: Introductionmentioning
confidence: 99%
“…SM is known in Sundanese as honje bereum (red) or honje laka. Several Etlingera study findings have been shown to exhibit pharmacological properties, including antibacterial [2], antidiabetic [3], cytotoxic action [4], protective impact against mercury chloride poisoning [5], and antioxidant [6]. The IC50 value of the methanol extract of kecombrang flower (Etlingera elatior Jack.)…”
Section: Introductionmentioning
confidence: 99%